2022
DOI: 10.1111/jdv.18109
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world efficacy and safety of dupilumab in Chinese patients with atopic dermatitis: a single‐centre, prospective, open‐label study

Abstract: Background Dupilumab, an antibody against interleukin-4 receptor a, has demonstrated elegant efficacy and safety profiles in patients with moderate-to-severe atopic dermatitis (AD). However, the efficacy of dupilumab varies among AD patients, and compared with the Caucasian population, the data of dupilumab for Asian people, especially Chinese AD patients, is very limited.Objective To investigate the efficacy and safety of dupilumab for AD in a real-world Chinese single-centre prospective cohort.Methods We enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 32 publications
6
16
0
Order By: Relevance
“…Although patients aged <6 years were treated with a high loading dose, the incidence of AEs did not increase during the treatment. Conjunctivitis and facial erythema were the most common AEs, consistent with previous studies ( 8 , 14 17 ). Our study suggested that dupilumab was a safe treatment for children, and a high loading dose could help to achieve rapid pruritus control.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although patients aged <6 years were treated with a high loading dose, the incidence of AEs did not increase during the treatment. Conjunctivitis and facial erythema were the most common AEs, consistent with previous studies ( 8 , 14 17 ). Our study suggested that dupilumab was a safe treatment for children, and a high loading dose could help to achieve rapid pruritus control.…”
Section: Discussionsupporting
confidence: 91%
“…The EASI75 response rate in patients aged >11 years of this study was comparable to the 42-84.6% rate reported in previous real-world studies in China (14-16). Weight, sex, age, clinical phenotypes, and serum lactate dehydrogenase levels might affect the efficacy of dupilumab treatment (14,34,35). Our study also highlighted that obesity predicted poor treatment outcomes, and females responded better to dupilumab treatment, which was in line with the findings of another study in China (14).…”
Section: B Amentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a larger regimen (Table 3) was partly administrated in our cohorts, which might further prove dupilumab a safe choice in pediatric patients, considering the low occurrence of adverse events. Conjunctivitis was the most commonly reported AE, with incidence rates in real-life studies ranging from 4.95% to 12.15% [12,[19][20][21][22][23][24], which was observed in 5.1% patients in our study. In the ≥2 to <6 years old group, one child experienced the injection-site reaction after the 2 nd injection, which resolved by itself.…”
Section: Discussionmentioning
confidence: 50%
“…Several novel systematic treatments have been suggested in the recent literature, including immunoglobulins and biologicals that target specific inflammatory pathways (4). Dupilumab, a monoclonal antibody that blocks the IL-4 receptor (IL-4R), has been used to treat moderate to severe atopic dermatitis with a good safety and efficacy profile (5). A few recent case report displayed clinical effect with improving skin symptoms in patients with NS who treated with dupilumab (6)(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%